Supporting Place-Specific Interaction through a Physical/Digital Assembly. (4th September 2018) - Ciolfi, Luigina; McLoughlin, Marc
Abstract : This article examines visitor interactions with and through a physical/digital installation designed for an open-air museum that displays historic buildings and ways of life from the past. The installation was designed following the "Assembly" design scheme proposed by Fraser et al. (2003 ), and centered around five principles for the design of interactive experiences. We discuss how the Assembly framework was adapted and applied to our work on the installation called Reminisce, and we then present qualitative data gathered through the shadowing and naturalistic observations of small groups of visitors using Reminisce during their exploration of the museum. Through these data excerpts, we illustrate how interaction occurred among visitors and with the assembly. We reflect on the guiding principles of the adapted Assembly framework and on their usefulness for the design of place-specific interactional opportunities in heritage settings. Results from the empirical study show that the adapted Assembly principles provide HCI (human–computer interaction) researchers and designers with ways in which to flexibly support collocated interactions at heritage sites across artifacts and locations in ways that both complement and enrich the physical setting of the visit and its character.